2022
DOI: 10.3389/fpubh.2022.1021200
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem inflammatory syndrome (MIS-C) with SARS-CoV-2 omicron variant BA.2.38 in a four-year-old Chinese girl: A case report

Abstract: We report a severe COVID-19 complicated with MIS-C in a girl treated by the author in China, and discuss the current research status and progress in the diagnosis and therapy of MIS-C in children. The patient was a 4-year-old child previously healthy who was referred to the hospital with a complaint of fever, finally, Multisystem inflammatory syndrome was diagnosed with COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Multisystem inflammatory syndrome in children is a rare post-infectious hyperinflammatory disorder associated with SARS-CoV-2 ( 25 ). Despite limited reports of MIS-C during the SARS-CoV-2 Omicron wave ( 26 , 27 ). In our cross sectional study, 12 patients were diagnosed with this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Multisystem inflammatory syndrome in children is a rare post-infectious hyperinflammatory disorder associated with SARS-CoV-2 ( 25 ). Despite limited reports of MIS-C during the SARS-CoV-2 Omicron wave ( 26 , 27 ). In our cross sectional study, 12 patients were diagnosed with this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, large MIS-C cohort studies from China, Japan, the Philippines, Thailand, Malaysia, and others were not identified. Extreme cases reported from Japan have shown the need for extracorporeal membrane oxygenation and continuous hemodiafiltration for MIS-C-related acute myocardial and renal injury and the potential benefit of infliximab in a patient with refractory MIS-C. [47][48][49][50] There are several limitations to our study. First, our study was conducted at a single tertiary referral center located in northern Taiwan.…”
Section: Re Sultsmentioning
confidence: 99%